Social Representations of Aging and Quality of Life in Riverine Old Age - de Cerqueira Castro, Jefferson Luiz (2021)
This study aimed to compare the Social Representations (SR) of aging and quality of life (QoL) in old age for riparian elderly. This is a qualitative-exploratory study with a non-probabilistic sample. Sociodemographic questionnaires and the free word association technique were used. Participants were 100 elderly, matched for sex, aged 60-89 years (M = 70.08 years; SD = 7.19). The IRaMuTeQ software was used through the prototypical analysis, which provided the representational structure. Negative central elements were observed in the SR of aging and more positive elements in the SR of QoL in old age, which denotes the welfare paradox; that is, positive self-reports of life satisfaction, even in the presence of aging losses.